Polymer and magnetic nanoparticle composites with tunable magneto-optical activity: role of nanoparticle dispersion for high verdet constant materials. Issue 16 (25th March 2020) - Pavlopoulos, N. G.; Kang, K. S.; Holmen, L. N.; Lyons, N. P.; Akhoundi, F.; Carothers, K. J.; Jenkins, S. L.; Lee, T.; Kochenderfer, T. M.; Phan, A.; Phan, D.; Mackay, M. E.; et al.
Abstract : The critical role of nanoparticle dispersion on Faraday rotator activity was studied, revealing new routes for fabricating "plastic garnets" as low cost alternatives to existing inorganic materials for optical isolation and magnetic sensing. Abstract : We report on a new strategy for preparing polymer–nanoparticle composite Faraday rotators for use in magnetic sensing and optical isolation. While most applications of Faraday rotators make use of inorganic garnet crystals, these are generally limited by low magneto-optical activity (low Verdet constants), high cost, and/or limited processing options. This has led to an interest in new materials with improved activity and processing characteristics. We have developed a new type of magneto-optical material based on polymer–nanoparticle composites that can be completely prepared by solution processing methods with tunable Verdet constants and device sensitivity. By exchanging native surface ligands on magneto-optically active CoFe2 O4 nanocrystals with polymer compatible ligands, enhanced nanoparticle dispersion in processible polymer matrices was observed at up to 15 wt% inorganic loading. Employing a multilayer polymer film construct, functional Faraday rotator devices were prepared by simple sequential spin-coating of active nanocomposite and protective, barrier cellulose acetate layers. For these assemblies, magneto-optic activity and sensitivity are easily tuned through variation of nanoparticle feed and control of polymer film layers, respectively. These multilayered Faraday rotators show up to a 10-fold enhancement in Verdet constant compared to reference terbium gallium garnets at 1310 nm, opening new possibilities for the fabrication of "plastic garnets" as low cost alternatives to existing inorganic materials for use in the near-IR.